Programming in parallel universes: Quantum computers could change the world beyond recognition - but will a working model ever be built? - Chown, Marcus (New Humanist)
The article focuses on the potential of quantum computers to change the world beyond recognition. It states that quantum computers have the potential to change the world as profoundly as electricity. It also states that laboratories around the world are stepping-stones on the road to building a useful quantum computers.